Phymatotrichum (cotton) root rot caused by Phymatotrichopsis omnivora: retrospects and prospects - UPPALAPATI, SRINIVASA RAO (Mol Plant Pathol, 2010)
Phymatotrichum (cotton or Texas) root rot is caused by the soil‐borne fungus Phymatotrichopsis omnivora (Duggar) Hennebert. The broad host range of the fungus includes numerous crop plants, such as alfalfa and cotton. Together with an overview of existing knowledge, this review is aimed at discussing the recent molecular and genomic approaches that have been undertaken to better understand the disease development at the molecular level with the ultimate goal of developing resistant germplasm. Taxonomy: Phymatotrichopsis omnivora (Duggar) Hennebert [synonym Phymatotrichum omnivorum (Shear) Duggar] is an asexual fungus with no known sexual stage. Mitosporic botryoblastospores occasionally form on epigeous spore mats in nature, but perform no known function and do not contribute to the disease cycle. The fungus has been affiliated erroneously with the polypore basidiomycete Sistotrema brinkmannii (Bres.) J. Erikss. Recent phylogenetic studies have placed this fungus in the ascomycete order Pezizales. Host range and disease symptoms: The fungus infects most dicotyledonous field crops, causing significant losses to cotton, alfalfa, grape, fruit and nut trees and ornamental shrubs in the south‐western USA, northern Mexico and possibly parts of central Asia. However, this fungus does not cause disease in monocotyledonous plants. Symptoms include an expanding tissue collapse (rot) of infected taproots. In above‐ground tissues, the root rot results in vascular discoloration of the stem and rapid wilting of the leaves without abscission, and eventually the death of the plant. Characteristic mycelial strands of the pathogen are typically present on the root's surface, aiding diagnosis. Pathogenicity: Confocal imaging of P. omnivora interactions with Medicago truncatula roots revealed that infecting hyphae do not form any specialized structures for penetration and mainly colonize cortical cells and eventually form a mycelial mantle covering the root's surfaces. Cell wall‐degrading enzymes have been implicated in penetration and symptom development. Global gene expression profiling of infected M. truncatula revealed roles for jasmonic acid, ethylene and the flavonoid pathway during disease development. Phymatotrichopsis omnivora apparently evades induced host defences and may suppress the host's phytochemical defences at later stages of infection to favour pathogenesis. Disease control: No consistently effective control measures are known. The long‐lived sclerotia and facultative saprotrophism of P. omnivora make crop rotation ineffective. Chemical fumigation methods are not cost‐effective for most crops. Interestingly, no genetic resistance has been reported in any of the susceptible crop species.